If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2 = -1 + 4x Reorder the terms: 2 + 5x = -1 + 4x Solving 2 + 5x = -1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2 + 5x + -4x = -1 + 4x + -4x Combine like terms: 5x + -4x = 1x 2 + 1x = -1 + 4x + -4x Combine like terms: 4x + -4x = 0 2 + 1x = -1 + 0 2 + 1x = -1 Add '-2' to each side of the equation. 2 + -2 + 1x = -1 + -2 Combine like terms: 2 + -2 = 0 0 + 1x = -1 + -2 1x = -1 + -2 Combine like terms: -1 + -2 = -3 1x = -3 Divide each side by '1'. x = -3 Simplifying x = -3
| P+9-4=58 | | 2x+42=-6x+18 | | 18-(-12)+(-8)= | | y=10(5)-1 | | d-3=-11 | | 8/42 | | y=10(1)-1 | | 1x2+3-4/2 | | 23+X=-85 | | 0=-16t^2+20t-4 | | y=10(0)-1 | | 5x+18=-4x+36 | | y=10(-1)-1 | | 5y-15=9y-19 | | y=10(-1)x-1 | | 16+3x=37 | | n/9=-5 | | 36-44+(-15)= | | 0=-16t^2-16t+60 | | y=-3(3)+3 | | 352/16=x-22 | | x+(5x-28)=180 | | y=-3(-3)+3 | | y(2y+3)=0 | | 0=-16t^2+1600 | | 20=a-(-8) | | (2x^2)+8x+11=0 | | 3(2g+12)=51+3g | | -1.3+y/7=-18.8 | | -7+x=4x+17 | | (y+3)(y+2)=0 | | 4n+3n=5(2-2n) |